The Post-illumination Pupil Response (PIPR) Is Associated With Cognitive Function in an Epidemiologic Cohort Study - Chen, Yanjun; Pinto, Alex A.; Paulsen, Adam J.; Schubert, Carla R.; Hancock, Laura M.; Klein, Barbara E.; Klein, Ron; Cruickshanks, Karen J. (Frontiers in Neurology, 2019)
We conducted a cross-sectional study on 403 participants in the 10-year follow-up examination of the Beaver Dam Offspring Study. The post-illumination pupil response (PIPR) was recorded using binocular infrared pupillometer (Neur-Optics, Inc., Irvine, CA). Cognitive testing consisted of Trail Making Test Parts A and B, Rey Auditory Verbal Learning Test, Digit Symbol Substitution Test, and Verbal Fluency Test (F, A, and S). Principal component analysis (PCA) was used to calculate an overall cognitive function score. The participants included 172 male and 231 female, with age ranging from 33 to 81 years (mean±SD, 60.7±9.3). There was a significant reduction in the mean baseline pupil diameter by 0.21 millimeter for every five-year increase in age (95% CI: -0.25, -0.17). There was also a significant increase in the PCA cognitive score by 0.20 (linear regression, 95% CI: 0.08, 0.32) for every 0.1 unit increase in the PIPR. The association remained significant after adjusting for age, sex, education, medications, systemic and ocular disease, and short form-12 physical and mental component score. The results of this study demonstrated a modest association between the PIPR and cognitive function, warranting longitudinal studies to evaluate the role of the PIPR in predicting cognitive function in the middle-aged and older adults.